Processed fish products based on diversification and standardization - Edy Purwanto; I. Isdiantoni; S. Syahril (Journal of Community Service and Empowerment, 2022)
Pagerungan Besar is one of the villages in Sapeken District, Sumenep Regency with the potential for marine products that are very plentiful. Business actors engaged in the fish processing industry in Pagerungan Besar Village are currently experiencing problems are understanding product diversification from processed fish and fish processing processes according to the Indonesian National Standard. This activity aims to provide an understanding to fishermen and business actors (processed fish) in Pagerungan Besar regarding innovative fish processed products and fish processing processes according to SNI Activities are carried out in the form of socialization and training. The service that is packaged in socialization and training activities has been prepared since Monday, May 31, 2021, and will be held on Friday, October 15, 2021, at the Pagerungan Besar Village Hall. Participants know the products that can be produced both during the pre-test and post-test. The results of the pre-test and post-test conducted showed that there was an increase in participants' knowledge of the SNI from 6 people (20%) to 30 people (100%). Participants' knowledge about product diversification from fish waste has increased significantly from 6 people (20%) to 30 people (100). Through this activity, participants gained a lot of knowledge in terms of product innovation, i.e., fish heads, tails, scales can be processed into high-value products and fish processing with Indonesian National Standards (Standar Nasional Indonesia/SNI).